INCREASING PARENT PARTICIPATION IN EARLY DETECTION AND DEVELOPMENT STIMULATION IN CHILDREN AGED 12-36 MONTHS - Sholihatul Amaliya; Nurona Azizah; Annisa Wuri Kartika; Ayut Merdikawati; Dina Nurpita Suprawoto; Nanda Aji Abiasukma; Alliya Avisa Insani Puteri (Caring : Jurnal Pengabdian Masyarakat, 2022)
Good quality children are closely related to optimal growth and development, especially in the three first years of life (toddler). The Covid-19 pandemic condition affects the level of parental visits to health facilities, thereby reducing the frequency of monitoring of child development by health workers. This condition increases the risk of delaying the discovery of a child's developmental disorder. Or community service activity is carried out to increase parental participation in screening and stimulating child development independently. The activity was carried out at the Delima Posyandu (Pos Pelayanan Terpadu) in the Puskesmas Gribig, area of Malang City in October 2021. The children involved in this activity were 12-36 months old, accompanied by parents or primary caregivers, and in healthy condition. Children suffering from acute illnesses such as fever, cough, diarrhea were not included in this activity. The activities consist of screening children's development with the Developmental Pre-Screening Questionnaire (KPSP) instrument and providing education with booklet media to parents on how to screen and stimulate development independently. Education was conducted on 24 parents individually and the results of developmental examinations showed that the majority of children had normal development or appropriate with their age, but more than a third of children had a doubt and delayed development. These results need to be a concern for health workers and “kader” to monitor the development of children in the area, especially those who have been detected had a doubt and delayed development